The Influence Between Self-Concept and Emotional Intelligence on The Ability of Physics Problem Solving - Palloan, P.; Usman, U.; Hakim, A. (Jurnal Pendidikan Fisika Indonesia, 2021)
This research aims to know the relationship between self-concept and emotional intelligence on the ability to solve the physics problem of students. The sample used was one hundred and fifteen people determined by simple random sampling. The ability to solve physics problems is measured by test instrument. The research data were processed using simple linear regression techniques and Â multiple regression. The results showed there was weak and significant positive relationship between self-concept and the ability to solve physics problems; there is very weak and insignificant positive relationship between emotional intelligence and the ability to solve physics problems; there is weak and significant positive relationship between self-concept and emotional intelligence together to the ability to solve physics problems.